2017
DOI: 10.7717/peerj.3208
|View full text |Cite
|
Sign up to set email alerts
|

Reproducible and reusable research: are journal data sharing policies meeting the mark?

Abstract: BackgroundThere is wide agreement in the biomedical research community that research data sharing is a primary ingredient for ensuring that science is more transparent and reproducible. Publishers could play an important role in facilitating and enforcing data sharing; however, many journals have not yet implemented data sharing policies and the requirements vary widely across journals. This study set out to analyze the pervasiveness and quality of data sharing policies in the biomedical literature.MethodsThe … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
110
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(125 citation statements)
references
References 25 publications
9
110
0
6
Order By: Relevance
“…For phylogenies, for example, it has been estimated that 60% of the data are not available to science [14]. Guidelines for sequence submission are standard for most journals, but such standards might not be true for other primary data; an analysis of the guidelines for authors of biomedical journals showed that only 12% of journals required general data sharing for publications [15]. Furthermore, the analysis presented here quantifies those studies that reported an accession number or link to sequence data, but it does not verify the quality of the attached metadata.…”
Section: Action To Ensure 'Open Sequencing Data'mentioning
confidence: 99%
“…For phylogenies, for example, it has been estimated that 60% of the data are not available to science [14]. Guidelines for sequence submission are standard for most journals, but such standards might not be true for other primary data; an analysis of the guidelines for authors of biomedical journals showed that only 12% of journals required general data sharing for publications [15]. Furthermore, the analysis presented here quantifies those studies that reported an accession number or link to sequence data, but it does not verify the quality of the attached metadata.…”
Section: Action To Ensure 'Open Sequencing Data'mentioning
confidence: 99%
“…Several studies explored compliance with journal data sharing policies [11][12][13][14][15]. For example, DAS in PLOS journals have been found to be significantly on the rise, after a mandated policy has been introduced, even if providing data in a repository remains a sharing method used only in a fraction of articles [16].…”
Section: Introductionmentioning
confidence: 99%
“…Issues such as publication bias 49,50 and low statistical power 51,52 have been discussed in the behavioral and biomedical sciences for decades and data stakeholders including scholarly publishers and federal funding agencies have instituted a range of reproducibility-related policies stipulating how the data underlying published work should be managed and shared. For example, while mandates requiring authors to share the data underlying publications have been shown to increase the degree to which data is made available 53 , only a minority of biomedical journals have such requirements and even fewer provide specific guidance as to how to make data available and reusable 54 . Federal funding bodies generally exercise their RDM-related policies by requiring that a data management 8/14 Table 6.…”
Section: Discussionmentioning
confidence: 99%